Selecting the Right Similarity‐Scoring Matrix. Issue 1 (16th February 2018) - Pearson, William R.
Abstract: Protein sequence similarity searching programs like BLASTP, SSEARCH, and FASTA use scoring matrices that are designed to identify distant evolutionary relationships (BLOSUM62 for BLAST, BLOSUM50 for SSEARCH and FASTA). Different similarity scoring matrices are most effective at different evolutionary distances. "Deep" scoring matrices like BLOSUM62 and BLOSUM50 target alignments with 20% to 30% identity, while "shallow" scoring matrices (e.g., VTML10 to VTML80) target alignments that share 90% to 50% identity, reflecting much less evolutionary change. While "deep" matrices provide very sensitive similarity searches, they also require longer sequence alignments and can sometimes produce alignment overextension into nonhomologous regions. Shallower scoring matrices are more effective when searching for short protein domains, or when the goal is to limit the scope of the search to sequences that are likely to be orthologous between recently diverged organisms. Likewise, in DNA searches, the match and mismatch parameters set evolutionary look‐back times and domain boundaries. In this unit, we will discuss the theoretical foundations that drive practical choices of protein and DNA similarity scoring matrices and gap penalties. Deep scoring matrices (BLOSUM62 and BLOSUM50) should be used for sensitive searches with full‐length protein sequences, but short domains or restricted evolutionary look‐back require shallower scoring matrices. Curr. Protoc. Bioinform . 43:3.5.1‐3.5.9. © 2013 by John Wiley & Sons, Inc.